Regional abnormalities in the hippocampus and verbal memory impairment in craniofacial dystonia - Liu, Gang; Liu, Huiming; Zhong, Linchang; Luo, Yuhan; Yang, Zhengkun; Zhang, Jiana; He, Xiuye; Ou, Zilin; Zhang, Weixi; Peng, Kangqiang; Xu, Jinping; Yan, Zhicong; et al. (Frontiers in Neuroscience, 2025)
BackgroundPatients with craniofacial dystonia (CFD) often present with verbal memory deficits, but their neuroanatomical basis is not yet clear. This study aims to determine whether verbal memory deficits in CFD are associated with structural atrophy of specific hippocampal subfields, and to isolate dystonia-specific pathological changes through comparison with patients with hemifacial spasm (HFS).MethodsWe recruited 50 patients with CFD, 48 patients with HFS, and 50 healthy controls (HCs). Verbal memory and global cognitive function were assessed using the Rey Auditory Verbal Learning Test (RAVLT) and the Mini-Mental State Examination (MMSE), respectively. Volumes of hippocampal subfields were quantified from high-resolution T1-weighted magnetic resonance imaging (MRI) using FreeSurfer. Group comparisons were performed after controlling for relevant covariates.ResultsWhile global cognition (MMSE) scores did not differ significantly among groups, patients with CFD demonstrated significant verbal memory deficits. Compared with HCs, they performed worse across immediate, short-, and long-delay recall trials, with medium-to-large effect sizes (all P-FDR ≤ 0.002; Cohen’s d = −0.70 to −0.82). Similar deficits of medium effect sizes were observed when compared with patients with HFS (all P-FDR ≤ 0.027; Cohen’s d = −0.49 to −0.52). Crucially, patients with HFS were unimpaired relative to HCs, establishing this memory deficit as specific to the dystonia pathophysiology. The imaging analysis revealed that patients with CFD were associated with significant atrophy in the left granule cell layer of the dentate gyrus (GC-DG) (P-FDR = 0.014; Cohen’s d = −0.58) and CA4 (P-FDR = 0.010; Cohen’s d = −0.60) compared with HCs, and with significant atrophy in the right GC-DG (P-FDR = 0.032; Cohen’s d = −0.52) and CA4 (P-FDR = 0.041; Cohen’s d = −0.50) compared with HCs. However, the magnitude of the atrophy showed no significant correlation with verbal memory scores, disease duration, or motor severity, revealing a critical structure-function dissociation.ConclusionOur findings reveal a structure-function dissociation in CFD. We propose its verbal memory deficits, despite hippocampal atrophy, may stem from broader network dysfunction or microstructural pathology not seen on conventional MRI. This challenges models assuming a direct link between macrostructural atrophy and cognitive symptoms.